Promoting Client Strength Through Positive Addiction - Glasser, William (Canadian Journal of Counselling and Psychotherapy, 2012)
Under certain conditions self-improvement activities like running or meditating can become addictive. This article contends that such addictions confer strength to the individual and promote effective living; therefore, they must be considered "positive". The article traces the development of theconcept of positive addiction (PA) and suggests that the construct will provevery useful to the counsellor who wishes to teach his or her clients how to help themselves grow stronger.